P100 EARLY POSTOPERATIVE WOUND COMPLICATIONS AFTER MIDLINE LAPAROTOMY CLOSURE WITH SMALL BITES TECHNIQUE: EXPERIENCE FROM A TERTIARY REFERRAL CENTRE. (25th November 2021) - Gudelis, Adomas; Simutis, Gintaras; Pacevicius, Julius
Abstract: Aim: To analyze the incidence and risk factors of surgical site infections (SSI) and wound dehiscence (WD) after closure of primary midline laparotomies with small-bites (SB) technique. Material and Methods: Retrospective analysis using hospital prospective database of all midline abdominal wall closures (AWC) with SB technique performed in a University Hospital between December 2019 and February 2021. To achieve a proper protocol of AWC with SB technique, it is advised to have suture/wound length (SL/WL) – ratio of more than 4:1. Statistical analysis of the incidence of SSI and AWD, comparing the results when the protocol was properly used (A group) or not (B group), was performed. Between groups, no relevant differences were observed for patient characteristics. Results: A total of 108 midline laparotomies were included for analysis. 55.5% of patients were male. The mean age was 62.8 years, mean body mass index was 24.3 kg/m 2 . 78.7% (85/108) were operated electively. SSI and WD have been recorded in 7 (6.5%) and 8 (7, 4%) cases respectively. In 65 (60, 2%) patients abdominal wall closure after primary laparotomy was achieved with proper protocol (group A). Median SL/WL in A and B group was 4.57 and 3.43 respectively. The rate of WD in A group (n = 1, 1, 5%) was significantly (P=.006) lower than in B group (n = 7, 16, 3%). Incidence of SSI was 7, 7% (n = 5, A group) vs. 4, 7% (n = 2; B group) (P=.420). Conclusions: Using a proper AWC protocol has been effective to prevent WD in midline laparotomy.